Belle of the Ball: Notions of Female Beauty in Jane Austen’s Pride and Prejudice and Mansfield Park - Kero, Santra (My University, 2024)
This thesis studies the definitions of female beauty within the context of the Regency era of England (1811-1820) as depicted in English writer Jane Austen’s two novels, Pride and Prejudice (1813) and Mansfield Park (1814). I examine the treatment and attitudes towards female characters who either fit into or diverge from the feminine beauty ideals of the Regency era. I first introduce central female beauty ideals of the time period and then consider how the female characters attempt to conform to or resist these ideals. As my study shows, the female characters featured in Pride and Prejudice and Mansfield Park offer different perspectives on female beauty. Portrayals of ideal beauty and femininity are presented by characters such as Jane Bennet and Mary Crawford while Elizabeth Bennet and Charlotte Lucas make a case for unconventional beauty or a complete lack of beauty. Additionally, I explore themes such as the correlation between aging and beauty, the interplay of beauty with social status, the significance of inner beauty versus outward appearance, and the implications of conventional beauty or lack thereof on a woman’s marriage prospects. Ultimately, the thesis shows that great value was placed on the appearance and feminine presentation of women. The constant pressure to perform beauty and femininity was prevalent within the strict expectations of the Regency society. The basis for my analysis is grounded in the writings of women’s rights advocate Mary Wollstonecraft as well as modern feminist thinkers such as Sandra Lee Bartky, Rose Weitz, and Naomi Wolf.
Keywords: Jane Austen, Pride and Prejudice, Mansfield Park, Regency era, beauty ideals, feminism